Social-Historical Development and Politics of Western Social Democracy and Socialist International (Part One: from World War I to 1989) - Kalik, Mario N.; Mitrović, Ratko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The history of Western social democracy and the Socialist International shows that it can hardly be a matter of true socialism and internationalism. On the inner and outer plan, it was primarily aimed at preserving capitalism and its defence against communism, while in the policy towards developing countries, marked by the association with imperialism and colonialism, it turned out that there was virtually nothing left of internationalism. Abandoning these principles (even in their weakened social-democratic form) unsurprisingly led the "modern" left in the West today to a major historical defence again. Consciously allying with the dominant neoliberal capitalist stream, Western social democrats gathered around the Socialist International explicitly saying they would not work on any alternative, or even a more radical break with the order of neoliberal capitalism. They thus become and remain a conservative social force. Therefore, they cannot be of any help to those who are still struggling against this order.